17‐a‐estradiol late in life extends lifespan in aging UM‐HET3 male mice; nicotinamide riboside and three other drugs do not affect lifespan in either sex. Issue 5 (31st March 2021) - Harrison, David E.; Strong, Randy; Reifsnyder, Peter; Kumar, Navasuja; Fernandez, Elizabeth; Flurkey, Kevin; Javors, Martin A.; Lopez‐Cruzan, Marisa; Macchiarini, Francesca; Nelson, James F.; Bitto, Alessandro; Sindler, Amy L.; et al.
Abstract: In genetically heterogeneous mice produced by the CByB6F1 x C3D2F1 cross, the "non‐feminizing" estrogen, 17‐α‐estradiol (17aE2), extended median male lifespan by 19% ( p  < 0.0001, log‐rank test) and 11% ( p  = 0.007) when fed at 14.4 ppm starting at 16 and 20 months, respectively. 90th percentile lifespans were extended 7% ( p  = 0.004, Wang–Allison test) and 5% ( p  = 0.17). Body weights were reduced about 20% after starting the 17aE2 diets. Four other interventions were tested in males and females: nicotinamide riboside, candesartan cilexetil, geranylgeranylacetone, and MIF098. Despite some data suggesting that nicotinamide riboside would be effective, neither it nor the other three increased lifespans significantly at the doses tested. The 17aE2 results confirm and extend our original reports, with very similar results when started at 16 months compared with mice started at 10 months of age in a prior study. The consistently large lifespan benefit in males, even when treatment is started late in life, may provide information on sex‐specific aspects of aging. Abstract : Interventions that increase lifespan when started late in life are most likely to be useful in the clinic. Testing genetically diverse mice, the "non‐feminizing" estrogen, 17‐α‐estradiol, extended median male lifespan by 19% ( p  < 0.0001, log‐rank test) and 11% ( p  = 0.007) when fed at 14.4 ppm starting at 16 and 20 months, respectively. Nicotinamide riboside and three other drugs did not affect lifespan in either sex.